(untitled) (PerCursos, 2021)
The term “climate change” has increasingly become part of the contemporary vocabulary, its effects being felt in the most different ways across the globe. However, this is not an exclusively recent phenomenon. The effects of climate change have influenced the ontology of human behavior, with striking expressions in its material culture, in a dual path of relationships, where the material culture itself serves as indicators of the environmental changes caused by climatic variations. In this sense, we propose a double approach methodology, based on analysis by fragmentation and intersection, as a way of understanding the complexity of climate / heritage relationships in the Serra da Capivara National Park region, Piaui, Brazil.